Advances in the Medical Management of Vascular Anomalies - Ricci, Kiersten W. (Seminars in Interventional Radiology, 2017)
Vascular anomalies comprise a spectrum of diseases that are broadly classified as tumors and malformations. Diagnosis is often challenging, given a wide range of clinical presentations with overlapping signs and symptoms. Accurate diagnosis is critical to determine prognosis and to generate a management plan, which frequently involves multiple subspecialists during different phases of treatment. An updated classification system provides structure and clear, consistent terminology, allowing for improved diagnosis, provider communication, and collaboration. Historically, treatment of vascular anomalies was primarily surgical and medical therapies were limited or ineffective. Recent discoveries of pharmacologic agents effective in treating vascular anomalies have broadened our medical therapeutic options, limiting the need for unnecessary or high-risk procedures and improving patients' quality of life.
Keywords: vascular anomaly; vascular malformation; sirolimus; propranolol; timolol; interventional radiology